The impact of an epilepsy nurse competency framework on the costs of supporting adults with epilepsy and intellectual disability: findings from the EpAID study. Issue 12 (8th August 2019) - Pennington, M.; Ring, H.; Howlett, J.; Smith, C.; Redley, M.; Murphy, C.; Hook, R.; Platt, A.; Gilbert, N.; Jones, E.; Kelly, J.; Pullen, A.; et al.
Abstract: Background: The development of a nurse‐led approach to managing epilepsy in adults with an intellectual disability (ID) offers the potential of improved outcomes and lower costs of care. We undertook a cluster randomised trial to assess the impact on costs and outcomes of the provision of ID nurses working to a designated epilepsy nurse competency framework. Here, we report the impact of the intervention on costs. Method: Across the United Kingdom, eight sites randomly allocated to the intervention recruited 184 participants and nine sites allocated to treatment as usual recruited 128 participants. Cost and outcome data were collected mainly by telephone interview at baseline and after 6 months. Total costs at 6 months were compared from the perspective of health and social services and society, with adjustments for pre‐specified participant and cluster characteristics at baseline including costs. Missing data were imputed using multiple imputation. Uncertainty was quantified by bootstrapping. Results: The intervention was associated with lower per participant costs from a health and social services perspective of −£357 (2014/2015 GBP) (95% confidence interval −£986, £294) and from a societal perspective of −£631 (95% confidence interval −£1473, £181). Results were not sensitive to the exclusion of accommodation costs. Conclusions: Our findings suggest that the competency framework is unlikely to increase the cost of caring for people with epilepsy and ID and may reduce costs.